PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024) - Anindya Azzahra; Ngatimin (Journal of Research and Publication Innovation, 2026)
This study to analyze the effect of profitability and leverage on tax aggressiveness in Consumer Non-Cyclials companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. Tax aggressiveness is measured by the Effective Tax Rate (ETR), while profitability is measured by Return On Equity (ROE) and leverage is measured by Debt to Asset (DAR). This research is quantitative and used annual financial reports as secondary data. The purposive sampling method was used to obtain 131 companies with a sampel of 46 observations. For data analysis, Eviews 12 was used to perform panel data regression analysis. The Random Effect Model (REM) based on the Lagrange Multiplier (LM) test was selected as the best model. The result of the study partially show that profitability has a significant negative effect on tax aggressiveness. Meanwhile, leverage has no effect on Tax Aggressiveness. Simultaneously, profitability and leverage have a significant effect on tax aggressiveness. The result, of this study are expected to be used as evaluation material for tax authorities in supervising corporate tax payers with high profitability levels.